Retroanalytical Study of Epidemiological Factors of Rhinosporidiosis - Mathew, Sairah; Arora, Ripu Daman; Prabha, Neel; Kamble, Payal; Satpute, Satish Suresh; Nagarkar, Nitin M. (International Archives of Otorhinolaryngology, 2020)
Introduction Rhinosporidiosis is a granulomatous disease of humans and animals that is caused by Rhinosporidium Seeberi. This disease is endemic in certain states of India, like Chhattisgarh, Tamil Nadu, Kerala, Orissa, and eastern Madhya Pradesh. We conducted a retrospective, record-based study in the department of ENT & Head and Neck Surgery of a tertiary case institute in Chhattisgarh.Objective To study the epidemiology of rhinosporidiosis, especially host risk factors.Methods We conducted a retrospective, record-based study in the department of ENT & Head and Neck Surgery of a tertiary case institute in Chhattisgarh, India. A total of 55 histologically proven rhinosporidiosis patients who were surgically treated in the department over a period of 2 years from November 2014 to November 2016 were included.Results This study involved 55 histologically proven rhinosporidiosis cases. There were 87% males and 12% females. Most of the cases belonged to lower socioeconomic status (92.73%). All the cases had history of pond bathing. Of 55 cases, 27 cases (49.09%) had O+ blood group followed by A+ in 10 (18.18%), B+ in 9 (16.36) and AB+ in 9 (16.36%).Conclusion The results of the study showed that the disease was associated with the male gender, young and middle age, low socioeconomic status, rural background, pond bathing and O+ blood group.
Keywords: rhinosporidiosis; epidemiology; host factors